2019
DOI: 10.1002/jsfa.10110
|View full text |Cite
|
Sign up to set email alerts
|

Nanoencapsulation of synergistic antioxidant fruit and vegetable concentrates and their stability during in vitro digestion

Abstract: BACKGROUND: Natural antioxidants have received increased attention owing to their safe use without side effects; however, their application has been limited because of lower antioxidant activity and stability during digestion when compared with those of synthetic antioxidants. Although research is ongoing to overcome these problems, it is still challenging to find effective solutions. In this study, we aimed to improve the properties and stability of natural antioxidants during in vitro digestion by synergisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Jeong, Lee, and Lee (2020) evaluated different combinations of fruit (açaí, aronia, blackberry, cranberry, wild berry, raspberry, blueberry, and red grape) and vegetable (spinach and cabbage) concentrates, when encapsulated in chitosan/gum arabic or chitosan/carrageenan nanoparticles. Authors determined that, during in vitro digestion, chitosan/gum Arabic particles were not stable, due to their increased polydispersity index.…”
Section: Nanotechnology Improving the Stabilitymentioning
confidence: 99%
“…Jeong, Lee, and Lee (2020) evaluated different combinations of fruit (açaí, aronia, blackberry, cranberry, wild berry, raspberry, blueberry, and red grape) and vegetable (spinach and cabbage) concentrates, when encapsulated in chitosan/gum arabic or chitosan/carrageenan nanoparticles. Authors determined that, during in vitro digestion, chitosan/gum Arabic particles were not stable, due to their increased polydispersity index.…”
Section: Nanotechnology Improving the Stabilitymentioning
confidence: 99%
“…Synergistic and antagonistic effects of observed activity of antioxidants have been repeatedly demonstrated (Du et al ., 2019; Oh et al ., 2019; Jeong et al ., 2020). One suggested mechanism for this is a ‘regeneration effect’, in which one antioxidant may regenerate another by absorbing its radical (Peyrat‐Maillard et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It also found that most of the phenolic compounds of raspberry fruit extract and berry did not change significantly after in vitro gastric digestion, which proved that phenolic compounds were relatively stable in acid gastric environment (Jeong et al. , 2020; Hao et al. , 2021).…”
Section: Resultsmentioning
confidence: 96%
“…As shown in Table 2, the contents of procyanidins, chlorogenic acid and all flavonols remained stable before and after gastric digestion (P > 0.05). It also found that most of the phenolic compounds of raspberry fruit extract and berry did not change significantly after in vitro gastric digestion, which proved that phenolic compounds were relatively stable in acid gastric environment (Jeong et al, 2020;Hao et al, 2021). However, EA in RLE after gastric digestion increased by 10%, which might be related to the hydrolysis of ellagitannin.…”
Section: Effects Of In Vitro Gastrointestinal Digestion On Phenolic Compoundsmentioning
confidence: 94%